Pakistan's Managerial Dilemmas (Distinguished Lecture) (The Pakistan Development Review, 1997)
Discretion without accountability is deeply rooted in Pakistan's political history, profoundly shaping the country's administrative system. Pakistan's political institutions offer the leadership many opportunities for violating citizen trust. Institutional change is proposed as a tool for politicians to maintain their authority through policy reform rather than patronage. Institutions are needed that allow politicians to lead while preserving the impartiality, permanence, and expertise of a public bureaucracy